A Novel Technique for Constructing Infectious Cloning of Type 3 Porcine Circovirus - Jiang, Zaixue; Wu, Jiajun; Jiang, Mei; Xie, Yilun; Bu, Wandi; Liu, Canbin; Zhang, Guihong; Luo, Manlin (Frontiers in Microbiology, 2020)
Porcine circovirus type 3 (PCV3), which currently lacks effective preventive measures, has caused tremendous economic losses to the pig husbandry. Obtaining the strain of the PCV3 is the key to preparing related vaccines and developing corresponding antiviral drugs. In this study, according to the linear sequence of PCV3 DNA published on Genbank, the sequence was rearranged with SnapGene gene editing software, and after rearrangement, the HindIII restriction endonuclease site was added to the end of the linear DNA, so that both ends have the same restriction endonuclease site. On this basis the rearranged linear DNA is obtained by gene synthesis, PCR amplification, DNA purification, etc., and is digested and connected in vitro to obtain cyclized DNA. PCV3 infectious clones were obtained by transfecting 3D4/21 cell lines. The obtained PCV3 was identified by PCR, Western blotting, and indirect immunofluorescence tests. The results showed that this study successfully obtained the strain of PCV3 in vitro. In order to further evaluate the pathogenicity of the obtained PCV3 infectious clones, this study established an animal model of Kunming mice infected with PCV3. The results of RT-PCR, Western blotting and immunohistochemistry showed that PCV3 can infect myocardium and alveoli of Kunming mice, but no PCV3 was detected in other tissues. The above studies indicate that PCV3 circular DNA can be used to construct PCV3 infectious clones. This research will provide a new method for the construction of circular DNA viruses and lay the foundation for the research and pathogenesis of PCV3 vaccine.